2021
DOI: 10.1002/mnfr.202100732
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AMPK Signaling by Dietary Polyphenols in Cancer Prevention

Abstract: Cancer is a serious public health problem in the world and a major disease affecting human health. Dietary polyphenols have shown good potential in the treatment of various cancers. It is worth noting that cancer cells usually exhibit metabolic abnormalities of high glucose intake and inefficient utilization. AMPK is the key molecule in the regulation of energy metabolism and is closely related with obesity and diabetes. Recent studies indicate that AMPK also plays an important role in cancer prevention and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 144 publications
(144 reference statements)
1
13
0
Order By: Relevance
“…Plant-derived bioactive compounds, especially polyphenolic, have shown to reduce tumorigenesis, interfering in the initiation, promotion and progression of cancer (Dana et al, 2022;George et al, 2021;Hu et al, 2022) including melanoma (Enaru et al, 2021;Khan et al, 2020;Musial et al, 2021;Patra et al, 2021;Pinto et al, 2021). Cytotoxic phytocompounds present in different species of the genera Rollinia (Araujo et al, 2021;Cunha et al, 2009) and other annonaceous (George et al, 2021;Handayani & Yuzammi, 2021;Khan et al, 2020;Perrone et al, 2022;Rocha et al, 2021;Shehata et al, 2021) support the experimental results obtained here, with selective cytotoxic effect on normal cells (Ribeiro et al, 2018;Shehata et al, 2021).…”
Section: Tablesupporting
confidence: 77%
See 1 more Smart Citation
“…Plant-derived bioactive compounds, especially polyphenolic, have shown to reduce tumorigenesis, interfering in the initiation, promotion and progression of cancer (Dana et al, 2022;George et al, 2021;Hu et al, 2022) including melanoma (Enaru et al, 2021;Khan et al, 2020;Musial et al, 2021;Patra et al, 2021;Pinto et al, 2021). Cytotoxic phytocompounds present in different species of the genera Rollinia (Araujo et al, 2021;Cunha et al, 2009) and other annonaceous (George et al, 2021;Handayani & Yuzammi, 2021;Khan et al, 2020;Perrone et al, 2022;Rocha et al, 2021;Shehata et al, 2021) support the experimental results obtained here, with selective cytotoxic effect on normal cells (Ribeiro et al, 2018;Shehata et al, 2021).…”
Section: Tablesupporting
confidence: 77%
“…Plants are an important source of natural compounds used for medicine, with considerable interest and special attention for their wide variety of bioactive metabolites. Several phytochemicals of different species have antitumor (Enaru et al, 2021;George et al, 2021;Hu et al, 2022;Khan et al, 2020;R.D.P. Nascimento et al, 2022;Patra et al, 2021) and antimicrobial activity (Christenhusz & Byng, 2016;Fernández et al, 2020;Marco et al, 2019;Vakayil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some phenolic compounds such as daidzein and genistein exhibited controversial effects on the pathogenesis of hormone-associated cancers ( 399 ). Such incongruous results have still not been reported for other phenolic categories, and it is now believed that PPs displayed their health-promising effects by interacting with various receptors and signaling pathways ( 551 ). In this respect, the emerging scientific investigations reported that supplementation of antioxidants (vitamin E and N-acetylcysteine) in mice increased the progression of lung cancer by inducing P53-assisted oxidative stress ( 198 ).…”
Section: Current Status and Future Perspectivesmentioning
confidence: 99%
“…Considering the numerous signal pathways involved in CRC metabolism, the exploration of multi‐target and safe natural bioactive compounds remained a priority (Ayan, Çetinkaya, Dursun, Güneş, & Şirin, 2021; Yang et al, 2021). Flavonoids are categorized as secondary metabolites, which were widely present in plant foods such as fruits, vegetables, whole grains, spices, herb plants, tea, and wine (Hu, Li, Cao, Guo, & Luo, 2021). In recent years, as dietary supplements or drug candidates, flavonoids are widely used to prevent CRC by targeting multiple signaling pathways in cancer metabolism, including signal pathway mediators such as oxidative stress, inflammation, and autophagy (Little, Combet, McMillan, Horgan, & Roxburgh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are categorized as secondary metabolites, which were widely present in plant foods such as fruits, vegetables, whole grains, spices, herb plants, tea, and wine (Hu, Li, Cao, Guo, & Luo, 2021). In recent years, as dietary supplements or drug candidates, flavonoids F I G U R E 1 Risk factors and general molecular mechanisms of CRC.…”
mentioning
confidence: 99%